Data-Informed Teaching and Action Research in Improving Evidence-Based Instruction - Alvin F. Consistente (Tecno Scientifica Publisher, 2026)
This explored the role of data-informed teaching and classroom action research in strengthening evidence-based instruction and improving student learning outcomes. The problem addressed centered on the persistent gap between the availability of educational data and its effective use in classroom decision-making, often resulting in less responsive and less effective teaching practices. The review aimed to synthesize existing literature on how teacher data literacy, action research, and continuous improvement models contributed to more systematic and evidence-driven instruction. It was hypothesized that integrating data-informed practices with iterative inquiry processes enhanced instructional quality and student achievement. Using a systematic review approach, relevant studies were analysed to identify key themes and relationships among data use, instructional strategies, and professional collaboration. The findings indicated that teacher data literacy was a critical foundation, enabling educators to interpret and apply data meaningfully. Classroom action research, particularly when conducted within Professional Learning Communities (PLCs), supported reflective practice and collaborative problem-solving. Evidence-based strategies such as explicit instruction, formative assessment, cooperative learning, metacognitive techniques, and timely feedback, were shown to be more effective when guided by data-driven insights. Furthermore, continuous improvement frameworks, especially the Plan-Do-Study-Act (PDSA) cycle, provided a structured process for refining instruction. The review concluded that the integration of data-informed teaching and action research fostered a culture of continuous improvement, professional growth, and accountability. Future studies should focus on the longitudinal impacts of these approaches, their scalability across diverse educational contexts, and the development of targeted interventions to strengthen teachers’ data literacy skills.